High-strength glazed large blocks for large-volume coke oven doors and their production process
By using alumina, Mo Lai Shi, hexagonal boron -nitride, and oxide, prepare large -volume coking furnace materials, and perform shock -resistant glaze hanging glaze treatment, solving existing furnace door materials High consumption problems achieve the effect of high strength, abrasion resistance and low energy consumption.
Patent Information
- Application Number
- CN202410958544.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-17
AI Technical Summary
The existing furnace door materials for large-volume coke ovens are prone to cracks, surface cracks, peeling and other problems during use, and the porosity of the material decreases, resulting in too fast heat transfer, which increases the energy consumption of coke oven sintering.
The use of alumina, Mo Lai stone, hexagonal boron -nitride, and oxide is used to prepare the body, and the glaze treatment is used to use the shock -resistant glaze to improve the refractory performance and anti -chemical erosion capacity of the block through the sintering process.
The mechanical strength, wear resistance and thermal shock resistance of the blocks are significantly improved, the service life is extended, physical damage and chemical corrosion during coke oven operation are reduced, and energy consumption is reduced.
Smart Images

Figure BDA0004949606330000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of furnace door brick preparation, in particular to a high-strength furnace door glaze large building block for a large-volume coke oven and a production process thereof. Background Art
[0002] Coke oven is a furnace made of refractory bricks and refractory blocks, usually used to gasify coal to produce coke, and is an important equipment with huge investment in the coking industry. Coke oven is composed of furnace wall, furnace roof, furnace bottom and furnace door. Generally, the service life of coke oven body is about 30 years, and the furnace door in the coke oven often needs to switch back and forth between ambient temperature and working temperature. In addition, it has to withstand the friction with coke when pushing coke, erosion of ash, slag, moisture and acidic gas, and carbon deposition, resulting in its service life generally being 1-3 years. Therefore, during the use of coke oven, the furnace door often needs to be repaired and cleaned, which affects the work efficiency and the repair environment is bad.
[0003] When preparing furnace door materials, the most commonly used method is to use composite additives to enhance the raw materials of furnace door bricks, such as using materials with lower thermal expansion coefficients such as cordierite to improve the resistance of furnace door to high temperature deformation, and using aluminate components to reduce the porosity of furnace door bricks to reduce the possibility of surface carbon accumulation. However, due to the increase in components, the factors affecting the change in the sintering performance of the material have also increased, so that the furnace door often has cracks, surface cracking, peeling and other problems after a period of use, resulting in higher requirements for the heat treatment process of sintering furnace door bricks. In addition, in order to avoid the adhesion of carbon deposits on the furnace door in the furnace, furnace door materials with low porosity are used to reduce the attachment sites of carbon on the furnace door. However, as the anti-carbon effect of the material increases, the porosity of the material also decreases, and the volume of air contained therein is also smaller, resulting in excessive heat transfer, which will increase the energy consumption of coke oven sintering. Therefore, a new high-strength furnace door glaze large block for large-volume coke ovens and its production process are needed. Summary of the invention
[0004] The object of the present invention is to provide a high-strength large glaze block for a large-volume coke oven door and a production process thereof, so as to solve the problems raised in the background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The production process of high-strength glazed large blocks for large-volume coke oven doors includes the following steps:
[0007] S1, placing the base powder of the green body in a mixer and stirring at 30-60 rpm for 10-20 minutes at room temperature, then adding a binder, continuing to stir for 10-20 minutes, and then transferring to a large block mold for pressing to obtain a primary green body;
[0008] S2. Glaze the preform prepared in step S1 with an anti-seismic glaze, and then sinter it in a kiln to obtain a high-strength glazed large building block for a large-volume coke oven door.
[0009] Furthermore, in step S1, the base powder of the green body includes the following raw materials in parts by weight:
[0010] 10-20 parts of Al2O3 powder with a particle size of 0.1-0.2mm, 10-15 parts of mullite with a particle size of 0.2-0.4mm, 10-15 parts of hexagonal boron nitride with a particle size of 0.2-0.4mm, 5-10 parts of Al2O3 powder with a particle size of 0.4-0.6mm, 10-15 parts of zirconium oxide powder with a particle size of 0.2-0.4mm, 5-10 parts of kaolin with a particle size of 0.2-0.4mm, 1.2-1.5 parts of cordierite with a particle size of 0.2-0.4mm and 3-5 parts of kyanite with a particle size of 0.2-0.4mm.
[0011] Furthermore, in step S1, the specific parameters of pressing are: pressure of 300-500 MPa, and pressing time of 10-20 minutes.
[0012] Furthermore, in step S1, the binder is at least one of polyvinyl alcohol, polyvinyl acetate, hydroxymethyl cellulose and paraffin, and the amount of the binder used is 5-10wt% of the base powder of the green body.
[0013] Further, in step S2, the anti-seismic glaze is prepared by the following steps:
[0014] The anti-seismic glaze is prepared by the following steps:
[0015] A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are placed in a 1-3 wt% chitosan solution and stirred until uniform, followed by ball milling for 1-3 hours to obtain a glaze base powder;
[0016] A2. Add ethyl orthosilicate to an ethanol solution, stir at room temperature for 10-30 minutes, then add 0 nitric acid solution, continue stirring for 5-10 minutes to obtain a silica sol; add the glaze base powder obtained in step A1 to the silica sol, then stir at room temperature for 10-30 minutes to obtain an anti-seismic glaze.
[0017] Further, in step S2, the anti-seismic glaze is prepared by the following steps:
[0018] A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are placed in a 1-3 wt% chitosan solution and stirred until uniform, followed by ball milling at a rate of 300-500 rpm for 1-3 hours to obtain a glaze base powder;
[0019] A2. Add 140-180 g of ethyl orthosilicate to 600-650 mL of 75 wt% ethanol solution, stir at room temperature for 10-30 minutes, then add 0.3-1.0 g of 10 wt% nitric acid solution, and continue stirring for 5-10 minutes to obtain silica sol; add the glaze base powder obtained in step A1 to the silica sol in a mass ratio of 1 g: (1-3) g, and then stir at room temperature for 10-30 minutes to obtain an anti-seismic glaze.
[0020] Furthermore, in step A1, the mass ratio of alumina powder, hexagonal boron nitride, sodium borate and magnesium oxide in the glaze base powder is (30-40):(5-10):(1-5):(1-5).
[0021] Furthermore, in step S2, the specific operation of the glazing treatment is as follows:
[0022] The blank obtained in step S1 is glazed with a brush at a rate of 100-120 g / m 2 Glaze the glaze with the amount of glaze, then air dry and glaze again at 100-120g / m 2 Apply one coat of glaze.
[0023] Furthermore, the specific operation of the sintering process is:
[0024] The glazed blank is transferred to the kiln and pre-sintered at 200-300°C. After 20-30 minutes of treatment, the temperature is increased to 1200-1400°C at a heating rate of 10-20°C / min. After 8 hours of treatment, it is slowly air-cooled to room temperature at a cooling rate of 50-100°C / min.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] In the technical solution of the present invention, the materials for preparing the blank are alumina, mullite, hexagonal boron nitride and zirconium oxide, and their combination can significantly improve the refractory performance and chemical erosion resistance of the building block. The high hardness and mechanical strength of alumina and mullite, the refractory performance and chemical erosion resistance of the building block improved by zirconium oxide powder, and the role of kaolin and hexagonal boron nitride in improving the overall plasticity, together enhance the mechanical strength and wear resistance of the building block. The addition of alumina powder of different particle sizes and cordierite and kyanite helps to optimize certain specific properties of the building block, such as thermal expansion coefficient, thermal shock resistance, etc.
[0027] In the process of mixing hexagonal boron nitride with ore components such as mullite, the trivalent boron ions in hexagonal boron nitride can enter the mullite crystal structure to replace Si, resulting in a decrease in the unit cell parameters and volume of the mullite, reducing the viscosity of the mullite system and promoting the diffusion rate of the components, which is conducive to the formation of a stable crystal structure of the ore components at a lower temperature and reducing the temperature required for sintering. The resulting blocks can be used at 1300°C without decomposition and transformation, and have the best spalling resistance and thermal expansion resistance, meeting the requirements for the use of furnace door bricks.
[0028] At the same time, during the firing process, anti-seismic glazes made of materials such as alumina powder, silica sol, and hexagonal boron nitride are added. Alumina powder, hexagonal boron nitride and other components are dissolved in silica sol to prepare anti-seismic glazes. During the sintering process of the glaze composed of the above components, silica sol can act as a high-temperature fusion agent for the components, forming a glass layer on the surface of the components to prevent solid-phase diffusion of aluminum atoms, etc., and can form a mullite crystal phase with quartz produced by heating of alumina, inhibiting the growth and deformation of flaky alumina, and participating in the network structure of amorphous ceramic materials through boron nitride and sodium borate components as network formers to form boron oxygen bonds with other elements, increasing the network connectivity of the glaze and the degree of adhesion on the surface of the block. In addition, the boron element changes the chemical composition ratio required for the formation of the spinel phase during the glaze sintering process, making the mullite phase the main crystal phase, and the boron element plays a catalyst role in the formation of crystal nuclei and crystal growth during the crystal phase transformation process, thereby accelerating the crystal phase transformation process, which can reduce the glaze sintering temperature and save energy. The glaze layer produced has high strength, good wear resistance and excellent corrosion resistance. It can effectively reduce the physical damage during the operation of the coke oven and the corrosion of refractory materials by chemicals such as tar, and reduce the friction with coke when pushing the coke oven door, thereby reducing the possibility of carbon deposition. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The compositions of the raw materials such as kaolin and cordierite used in the following examples and comparative examples are shown in Table 1 below.
[0031] Table 1 Raw material composition
[0032]
[0033]
[0034] Example 1
[0035] The production process of high-strength glazed large blocks for large-volume coke oven doors includes the following steps:
[0036] S1, placing the green body base powder in a mixer and stirring at 30 rpm for 10 minutes at room temperature, then adding 5 wt% polyvinyl alcohol binder, continuing to stir for 10 minutes, and then transferring to a large block mold for pressing, setting the pressure to 300 MPa, and pressing time for 10 minutes to obtain a green body;
[0037] Among them, the green body base powder includes the following raw materials by weight:
[0038] 10 parts of Al2O3 powder with a particle size of 0.1-0.2 mm, 10 parts of mullite with a particle size of 0.2-0.4 mm, 10 parts of hexagonal boron nitride with a particle size of 0.2-0.4 mm, 5 parts of Al2O3 powder with a particle size of 0.4-0.6 mm, 10 parts of zirconium oxide powder with a particle size of 0.2-0.4 mm, 5 parts of kaolin with a particle size of 0.2-0.4 mm, 1.2 parts of cordierite with a particle size of 0.2-0.4 mm and 3 parts of kyanite with a particle size of 0.2-0.4 mm;
[0039] S2, glaze the preform prepared in step S1 with anti-seismic glaze, apply glaze with a brush at a glaze amount of 110g per square meter, then air-dry and apply glaze again at a glaze amount of 110g / m 2 The glaze is applied once, and then the glazed blank is transferred to the kiln, and pre-sintered at 200°C for 20 minutes, and then the temperature is increased to 1200°C at a heating rate of 10°C / min. After 8 hours of treatment, the blank is slowly air-cooled to room temperature at a cooling rate of 50°C / min, and a high-strength glazed large block for large-volume coke oven door is obtained;
[0040] Wherein, the earthquake-resistant glaze is prepared by the following steps:
[0041] A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are mixed in a mass ratio of 30:5:1:1, and the obtained mixture is placed in a 1 wt% chitosan solution in a mass volume ratio of 1 g:10 mL and stirred until uniform, and then ball milled at a speed of 300 rpm for 1-3 hours to obtain a glaze base powder;
[0042] A2. Add 140 g of tetraethyl orthosilicate to 600 mL of 75 wt% ethanol solution, stir at room temperature for 10 minutes, then add 0.2 g of 10 wt% nitric acid solution, and continue stirring for 5 minutes to obtain silica sol; add the glaze base powder obtained in step A1 to the silica sol in a mass ratio of 1 g: 1 g, and then stir at room temperature for 10 minutes to obtain an anti-seismic glaze.
[0043] Example 2
[0044] The production process of high-strength glazed large blocks for large-volume coke oven doors includes the following steps:
[0045] S1, placing the green body base powder in a mixer and stirring at 40 rpm for 15 minutes at room temperature, then adding 5 wt% polyvinyl alcohol binder, continuing to stir for 15 minutes, and then transferring to a large block mold for pressing, setting the pressure to 400 MPa, and pressing time for 15 minutes to obtain a primary green body;
[0046] Among them, the green body base powder includes the following raw materials by weight:
[0047] 15 parts of Al2O3 powder with a particle size of 0.1-0.2 mm, 13 parts of mullite with a particle size of 0.2-0.4 mm, 12 parts of hexagonal boron nitride with a particle size of 0.2-0.4 mm, 8 parts of Al2O3 powder with a particle size of 0.4-0.6 mm, 13 parts of zirconium oxide powder with a particle size of 0.2-0.4 mm, 8 parts of kaolin with a particle size of 0.2-0.4 mm, 1.3 parts of cordierite with a particle size of 0.2-0.4 mm and 4 parts of kyanite with a particle size of 0.2-0.4 mm;
[0048] S2, glaze the preform prepared in step S1 with anti-seismic glaze, apply glaze with a brush at a glaze amount of 110g per square meter, then air-dry and apply glaze again at a glaze amount of 110g / m 2 The glaze is applied once, and then the glazed blank is transferred to the kiln, and pre-sintered at 250°C. After 25 minutes of treatment, the temperature is increased to 1300°C at a heating rate of 15°C / min. After 8 hours of treatment, it is slowly air-cooled to room temperature at a cooling rate of 80°C / min, and a high-strength glazed large block for large-volume coke oven door is obtained;
[0049] Wherein, the earthquake-resistant glaze is prepared by the following steps:
[0050] A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are mixed in a mass ratio of 35:7:3:3, and the obtained mixture is placed in a 2wt% chitosan solution in a mass volume ratio of 1 g:10 mL and stirred until uniform, and then ball milled at a speed of 400 rpm for 1-3 hours to obtain a glaze base powder;
[0051] A2. Add 160 g of ethyl orthosilicate to 620 mL of 75 wt% ethanol solution, stir at room temperature for 20 minutes, then add 0.6 g of 10 wt% nitric acid solution, and continue stirring for 8 minutes to obtain silica sol; add the glaze base powder obtained in step A1 to the silica sol in a mass ratio of 1 g: 2 g, and then stir at room temperature for 20 minutes to obtain an anti-seismic glaze.
[0052] Example 3
[0053] The production process of high-strength glazed large blocks for large-volume coke oven doors includes the following steps:
[0054] S1, placing the green body base powder in a mixer and stirring at 60 rpm for 20 minutes at room temperature, then adding 5 wt% polyvinyl alcohol binder, continuing to stir for 20 minutes, and then transferring to a large block mold for pressing, setting the pressure to 500 MPa, and pressing time for 20 minutes to obtain a primary green body;
[0055] Among them, the green body base powder includes the following raw materials by weight:
[0056] 20 parts of Al2O3 powder with a particle size of 0.1-0.2 mm, 15 parts of mullite with a particle size of 0.2-0.4 mm, hexagonal boron nitride with a particle size of 0.2-0.4 mm, 0.4-0.6 mm Al2O3 powder, 15 parts of zirconium oxide powder with a particle size of 0.2-0.4 mm, 10 parts of kaolin with a particle size of 0.2-0.4 mm, 1.5 parts of cordierite with a particle size of 0.2-0.4 mm and 5 parts of kyanite with a particle size of 0.2-0.4 mm;
[0057] S2, glaze the preform prepared in step S1 with anti-seismic glaze, apply glaze with a brush at a glaze amount of 110g per square meter, then air-dry and apply glaze again at a glaze amount of 110g / m 2 The glaze is applied once, and then the glazed blank is transferred to the kiln, and pre-sintered at 300°C. After 30 minutes of treatment, the temperature is increased to 1400°C at a heating rate of 20°C / min. After 8 hours of treatment, it is slowly air-cooled to room temperature at a cooling rate of 100°C / min, and a high-strength glazed large block for large-volume coke oven door is obtained;
[0058] Wherein, the earthquake-resistant glaze is prepared by the following steps:
[0059] A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are mixed in a mass ratio of 40:10:5:5, and the obtained mixture is placed in a 3 wt % chitosan solution in a mass volume ratio of 1 g:10 mL and stirred until uniform, and then ball milled at a speed of 500 rpm for 1-3 hours to obtain a glaze base powder;
[0060] A2. Add 180 g of ethyl orthosilicate to 650 mL of 75 wt% ethanol solution, stir at room temperature for 30 minutes, then add 1.0 g of 10 wt% nitric acid solution, and continue stirring for 10 minutes to obtain silica sol; add the glaze base powder obtained in step A1 to the silica sol in a mass ratio of 1 g:3 g, and then stir at room temperature for 30 minutes to obtain an anti-seismic glaze.
[0061] Comparative Example 1
[0062] The production process of high-strength glazed large blocks for large-volume coke oven doors includes the following steps:
[0063] S1, placing the green body base powder in a mixer and stirring at 30 rpm for 10 minutes at room temperature, then adding 5 wt% polyvinyl alcohol binder, continuing to stir for 10 minutes, and then transferring to a large block mold for pressing, setting the pressure to 300 MPa, and pressing time for 10 minutes to obtain a green body;
[0064] Among them, the green body base powder includes the following raw materials by weight:
[0065] 10 parts of Al2O3 powder with a particle size of 0.1-0.2 mm, 20 parts of mullite with a particle size of 0.2-0.4 mm, 5 parts of Al2O3 powder with a particle size of 0.4-0.6 mm, 10 parts of zirconium oxide powder with a particle size of 0.2-0.4 mm, 5 parts of kaolin with a particle size of 0.2-0.4 mm, and 4.2 parts of kyanite with a particle size of 0.2-0.4 mm;
[0066] S2, glaze the preform prepared in step S1 with anti-seismic glaze, apply glaze with a brush at a glaze amount of 110g per square meter, then air-dry and apply glaze again at a glaze amount of 110g / m 2 The glaze is applied once, and then the glazed blank is transferred to the kiln, and pre-sintered at 200°C for 20 minutes, and then the temperature is increased to 1200°C at a heating rate of 10°C / min. After 8 hours of treatment, the blank is slowly air-cooled to room temperature at a cooling rate of 50°C / min, and a high-strength glazed large block for large-volume coke oven door is obtained;
[0067] Wherein, the earthquake-resistant glaze is prepared by the following steps:
[0068] A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are mixed in a mass ratio of 30:5:1:1, and the obtained mixture is placed in a 1 wt% chitosan solution in a mass volume ratio of 1 g:10 mL and stirred until uniform, and then ball milled at a speed of 300 rpm for 1-3 hours to obtain a glaze base powder;
[0069] A2. Add 140 g of tetraethyl orthosilicate to 600 mL of 75 wt% ethanol solution, stir at room temperature for 10 minutes, then add 0.2 g of 10 wt% nitric acid solution, and continue stirring for 5 minutes to obtain silica sol; add the glaze base powder obtained in step A1 to the silica sol in a mass ratio of 1 g: 1 g, and then stir at room temperature for 10 minutes to obtain an anti-seismic glaze.
[0070] Comparative Example 2
[0071] The difference between this comparative example and Example 1 is that sodium borate and hexagonal boron nitride are not used in the glaze base powder.
[0072] The production process of high-strength glazed large blocks for large-volume coke oven doors includes the following steps:
[0073] S1, placing the green body base powder in a mixer and stirring at 30 rpm for 10 minutes at room temperature, then adding 5 wt% polyvinyl alcohol binder, continuing to stir for 10 minutes, and then transferring to a large block mold for pressing, setting the pressure to 300 MPa, and pressing time for 10 minutes to obtain a green body;
[0074] Among them, the green body base powder includes the following raw materials by weight:
[0075] 10 parts of Al2O3 powder with a particle size of 0.1-0.2 mm, 10 parts of mullite with a particle size of 0.2-0.4 mm, 10 parts of hexagonal boron nitride with a particle size of 0.2-0.4 mm, 5 parts of Al2O3 powder with a particle size of 0.4-0.6 mm, 10 parts of zirconium oxide powder with a particle size of 0.2-0.4 mm, 5 parts of kaolin with a particle size of 0.2-0.4 mm, 1.2 parts of cordierite with a particle size of 0.2-0.4 mm and 3 parts of kyanite with a particle size of 0.2-0.4 mm;
[0076] S2, glaze the preform prepared in step S1 with anti-seismic glaze, apply glaze with a brush at a glaze amount of 110g per square meter, then air-dry and apply glaze again at a glaze amount of 110g / m 2 The glaze is applied once, and then the glazed blank is transferred to the kiln, and pre-sintered at 200°C for 20 minutes, and then the temperature is increased to 1200°C at a heating rate of 10°C / min. After 8 hours of treatment, the blank is slowly air-cooled to room temperature at a cooling rate of 50°C / min, and a high-strength glazed large block for large-volume coke oven door is obtained;
[0077] Wherein, the earthquake-resistant glaze is prepared by the following steps:
[0078] A1. Alumina powder with a particle size of 0.5-1 μm and magnesium oxide are mixed in a mass ratio of 30:1, and the obtained mixture is placed in a 1 wt% chitosan solution in a mass volume ratio of 1 g:10 mL and stirred until uniform, and then ball-milled at a speed of 300 rpm for 1-3 hours to obtain a glaze base powder;
[0079] A2. Add 140 g of tetraethyl orthosilicate to 600 mL of 75 wt% ethanol solution, stir at room temperature for 10 minutes, then add 0.2 g of 10 wt% nitric acid solution, and continue stirring for 5 minutes to obtain silica sol; add the glaze base powder obtained in step A1 to the silica sol in a mass ratio of 1 g: 1 g, and then stir at room temperature for 10 minutes to obtain an anti-seismic glaze.
[0080] Comparative Example 3
[0081] The difference between this comparative example and implementation 1 is that no gradient is set for sintering. The sintering is directly performed for 8.5 hours. The production process of high-strength glazed large blocks for large-volume coke oven doors comprises the following steps:
[0082] S1, placing the green body base powder in a mixer and stirring at 30 rpm for 10 minutes at room temperature, then adding 5 wt% polyvinyl alcohol binder, continuing to stir for 10 minutes, and then transferring to a large block mold for pressing, setting the pressure to 300 MPa, and pressing time for 10 minutes to obtain a green body;
[0083] Among them, the green body base powder includes the following raw materials by weight:
[0084] 10 parts of Al2O3 powder with a particle size of 0.1-0.2 mm, 10 parts of mullite with a particle size of 0.2-0.4 mm, 10 parts of hexagonal boron nitride with a particle size of 0.2-0.4 mm, 5 parts of Al2O3 powder with a particle size of 0.4-0.6 mm, 10 parts of zirconium oxide powder with a particle size of 0.2-0.4 mm, 5 parts of kaolin with a particle size of 0.2-0.4 mm, 1.2 parts of cordierite with a particle size of 0.2-0.4 mm and 3 parts of kyanite with a particle size of 0.2-0.4 mm;
[0085] S2, glaze the preform prepared in step S1 with anti-seismic glaze, apply glaze with a brush at a glaze amount of 110g per square meter, then air-dry and apply glaze again at a glaze amount of 110g / m 2 The glaze is applied once, and then the glazed blank is transferred to the kiln, and the temperature is first increased to 1200°C at a heating rate of 10°C / min. After 8.3 hours of treatment, it is slowly air-cooled to room temperature at a cooling rate of 50°C / min, and a high-strength glazed large block for large-volume coke oven door is obtained;
[0086] Wherein, the earthquake-resistant glaze is prepared by the following steps:
[0087] A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are mixed in a mass ratio of 30:5:1:1, and the obtained mixture is placed in a 1 wt% chitosan solution in a mass volume ratio of 1 g:10 mL and stirred until uniform, and then ball milled at a speed of 300 rpm for 1-3 hours to obtain a glaze base powder;
[0088] A2. Add 140 g of tetraethyl orthosilicate to 600 mL of 75 wt% ethanol solution, stir at room temperature for 10 minutes, then add 0.2 g of 10 wt% nitric acid solution, and continue stirring for 5 minutes to obtain silica sol; add the glaze base powder obtained in step A1 to the silica sol in a mass ratio of 1 g: 1 g, and then stir at room temperature for 10 minutes to obtain an anti-seismic glaze.
[0089] The large blocks prepared in Examples 1-3 and Comparative Examples 1-3 are now subjected to quality tests. Block samples with a size of 0.15m*0.12m*0.08m are prepared, and the blocks are visually inspected for defects such as cracks, bubbles, and poor sintering. The block samples are then heated to 1500°C and then air-cooled. After 10 cycles, the coking condition on the sample surface is observed, and the thermal insulation effect of the material is tested. Subsequently, the thermal shock stability test is continued according to the temperature cycle of 1500°C-air cooling. Five readings are obtained for each sample and the average value is taken. The test results are shown in Table 2 below.
[0090] Table 2 Quality test of large blocks prepared in Examples 1-3 and Comparative Examples 1-3
[0091] project Thermal shock stability Thermal conductivity (W / (m·K)) Example 1 210 0.37 Example 2 220 0.34 Example 3 210 0.36 Comparative Example 1 200 0.42 Comparative Example 2 160 0.49 Comparative Example 3 180 0.40
[0092] After appearance inspection, the block samples in the embodiments all have complete surfaces, without defects such as cracks, bubbles, and poor sintering. It can be seen that the glaze layer of the block samples prepared in the embodiments shows high stability and has a good bonding effect with the green body. As can be seen from the results in Table 2, the block samples prepared in Example 2 show the best thermal shock stability and the best thermal insulation effect. As can be seen from the results in Comparative Examples 1 and 2, the use of hexagonal boron nitride, sodium borate, cordierite and other components in the block components can effectively regulate the crystal phase transformation of the blocks during the sintering process, and obtain block samples with better performance. After ten temperature cycles, the samples in the three embodiments did not show surface coking, nor did they carbonize and peel off. As can be seen from the results in Comparative Example 3, setting a pre-sintering process can better improve the bonding effect between the glaze and the green body.
[0093] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0094] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. The production process of high-strength glazed large blocks for large-volume coke oven doors is characterized in that: The following steps are involved: S1, placing the base powder of the green body in a mixer and stirring at 30-60 rpm for 10-20 minutes at room temperature, adding a binder, continuing to stir for 10-20 minutes, and then transferring to a large block mold for pressing to obtain a primary green body; Wherein, the green body base powder includes the following raw materials by weight: 10-20 parts of Al2O3 powder with a particle size of 0.1-0.2mm, 10-15 parts of mullite with a particle size of 0.2-0.4mm, 10-15 parts of hexagonal boron nitride with a particle size of 0.2-0.4mm, 5-10 parts of Al2O3 powder with a particle size of 0.4-0.6mm, 10-15 parts of zirconium oxide powder with a particle size of 0.2-0.4mm, 5-10 parts of kaolin with a particle size of 0.2-0.4mm, 1.2-1.5 parts of cordierite with a particle size of 0.2-0.4mm and 3-5 parts of kyanite with a particle size of 0.2-0.4mm; S2, using an anti-seismic glaze to glaze the preform prepared in step S1, and then sintering it in a kiln to obtain a high-strength glazed large building block for a large-volume coke oven door; Wherein, the earthquake-resistant glaze is prepared by the following steps: A1. Alumina powder with a particle size of 0.5-1 μm, hexagonal boron nitride, sodium borate and magnesium oxide are placed in a 1-3 wt% chitosan solution and stirred until uniform, followed by ball milling for 1-3 hours to obtain a glaze base powder; the mass ratio of alumina powder, hexagonal boron nitride, sodium borate and magnesium oxide in the glaze base powder is (30-40): (5-10): (1-5): (1-5); A2. Add ethyl orthosilicate to an ethanol solution, stir at room temperature for 10-30 minutes, then add a nitric acid solution, and continue stirring for 5-10 minutes to obtain a silica sol; add the glaze base powder obtained in step A1 to the silica sol, then stir at room temperature for 10-30 minutes to obtain an anti-seismic glaze.
2. The production process of high-strength glazed large building blocks for large-volume coke oven doors according to claim 1 is characterized in that: In step S1, the specific parameters of pressing are: pressure of 300-500 MPa, and pressing time of 10-20 minutes.
3. The production process of high-strength glazed large building blocks for large-volume coke oven doors according to claim 1 is characterized in that: In step S1, the binder is at least one of polyvinyl alcohol, polyvinyl acetate, hydroxymethyl cellulose and paraffin, and the amount of the binder used is 5-10wt% of the base powder of the green body.
4. The production process of high-strength glazed large building blocks for large-volume coke oven doors according to claim 1 is characterized in that: In step S2, the specific operation of the glazing treatment is as follows: The blank obtained in step S1 is glazed with a brush at a rate of 100-120 g / m 2 Glaze the glaze with the amount of glaze, then air dry and glaze again at 100-120g / m 2 Apply one coat of glaze.
5. The production process of high-strength glazed large building blocks for large-volume coke oven doors according to claim 1 is characterized in that: In step S2, the specific operation of the sintering process is: The glazed blank is transferred to the kiln and pre-sintered at 200-300°C. After 20-30 minutes of treatment, the temperature is increased to 1200-1400°C at a heating rate of 10-20°C / min. After 8 hours of treatment, it is slowly air-cooled to room temperature at a cooling rate of 50-100°C / min.
6. A block made by the production process of large high-strength glazed blocks for large-volume coke oven doors as claimed in any one of claims 1 to 5.
Citation Information
Patent Citations
Castable of non-wetting hard aluminum alloy and preparation process of castable
CN112094126A
Furnace door glazed large building block for large-volume coke oven, and production process thereof
CN112745131A